The Meaning of Social Interaction in Tauh Dance Jambi Society: A Performing Arts Perspective - Tri Putra Mahardhika. H; Angeline Azhar; Sania Putri Oktaviani Andriyanti; Ricky Subagja; Fajar Hidayatulloh (Pascasarjana ISBI Bandung Conference Series, 2025)
The Tauh dance of the Jambi community, as a performance art rich in meaning, reflects the social interactions and daily life of its people. This article analyzes the meaning of social interactions in the Tauh dance through a literature study. Its distinctive movements, musical rhythms, and visual elements serve as a medium for communicating the values and social norms of the Jambi community. The research concludes that the Tauh dance is not merely entertainment, but a profound artistic narrative that depicts life, resistance against colonizers, and the collective values of the Jambi community. Keywords: Tauh dance; jambi community; performing arts